Kurikulum Merdeka: Pendampingan Pembelajaran Berdiferensiasi bagi Guru SD di Wonosobo dan Banjarnegara - Siti Aimah; Bambang Purwanto; Wiyaka Wiyaka; Divya Fitriyani; Elmira Noer Shaumi; Nurani Ayu Febriana (Jurnal Surya Masyarakat, 2025)
The lack of comprehension of the Merdeka Curriculum among elementary school teachers generally affects how they implement differentiated learning in the classroom. This program aims to 1) assist elementary school teachers with the Merdeka Curriculum; 2) assist elementary teachers with the student diversity in differentiated learning; and 3) share best practices in differentiated learning implementation with elementary teachers. To accomplish the aforementioned goals, especially for 24 primary school teachers, a variety of strategies were used, including offline and online workshops. The findings of the interview and the workshop observations indicate that elementary school teachers' comprehension of the Merdeka curriculum has improved. To assist them in putting differentiated learning into practice, the majority of them are adept at modifying the teaching module (MA), which covers understanding learning outcomes (CP), expanding them into learning objectives (TP), and so on. Elementary school teachers in Kab. Banjarnegara & Kab. Wonosobo now have a greater knowledge of differentiated learning in the classroom and the Merdeka curriculum after attending the workshops. It is intended that teachers can completely incorporate differentiated learning into the classroom to provide students with relevant learning experiences.